2016
DOI: 10.1063/1.4947071
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative protein structural dynamics of homodimeric hemoglobin linked to water cluster at subunit interface revealed by time-resolved X-ray solution scattering

Abstract: Homodimeric hemoglobin (HbI) consisting of two subunits is a good model system for investigating the allosteric structural transition as it exhibits cooperativity in ligand binding. In this work, as an effort to extend our previous study on wild-type and F97Y mutant HbI, we investigate structural dynamics of a mutant HbI in solution to examine the role of well-organized interfacial water cluster, which has been known to mediate intersubunit communication in HbI. In the T72V mutant of HbI, the interfacial water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 58 publications
(30 reference statements)
1
26
0
Order By: Relevance
“…86, [332][333][334][335][336] Later, the same groups embarked in the study of dimeric hemoproteins, 337,338 with the aim to investigate cooperativity. Solution ps XRS is ideal when looking at conformational changes, large amplitude side chain motions and folding-unfolding processes and the above studies revealed several hitherto unknown details of the large scale protein dynamics.…”
Section: Picosecond Studiesmentioning
confidence: 99%
“…86, [332][333][334][335][336] Later, the same groups embarked in the study of dimeric hemoproteins, 337,338 with the aim to investigate cooperativity. Solution ps XRS is ideal when looking at conformational changes, large amplitude side chain motions and folding-unfolding processes and the above studies revealed several hitherto unknown details of the large scale protein dynamics.…”
Section: Picosecond Studiesmentioning
confidence: 99%
“…However, the allosteric structural transition of Hb is still elusive because of the complex kinetics arising from its heteromeric tetramer structure. In this respect, homodimeric hemoglobin (HbI) from Scapharca inaequivalvis has served as an excellent model system for investigating the allosteric structural transition between a ligated R state with high ligand affinity and a deoxygenated T state with low ligand affinity [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] due to its simpler dimeric structure. In the HbI, the E and F helices of monomers are located at the interface of homodimer [ 11 , 12 , 39 ], which is often referred to as EF dimer.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to dissect individual conformational motions and measure their rates using time-resolved X-ray measurements is important for understanding processes involving complex protein dynamics. Many of these dynamic processes, including allostery (Colombo et al, 1992;Kim et al, 2016;Royer et al, 1996;Salvay et al, 2003) and enzyme catalysis (Decaneto et al, 2017;Fenwick et al, 2018;Grossman et al, 2011;Guha et al, 2005;Leidner et al, 2018), involve extensive reorganization of interactions between the protein and its ordered solvation shell, which are key contributors to the energetics that govern protein motions (Caro et al, 2017;Conti Nibali et al, 2014;Dahanayake and Mitchell-Koch, 2018;Fenimore et al, 2002;Frauenfelder et al, 2007;Gavrilov et al, 2017;Wand and Sharp, 2018). Because X-ray solution scattering experiments report on the structure of a protein and the ordered solvent molecules that constitute its solvation shell (Henriques et al, 2018;Hub, 2018;Svergun et al, 1998;Virtanen et al, 2011), the widespread application of time-resolved SAXS/WAXS experiments will enhance our understanding of how protein motions are driven by solvent dynamics, especially when they can be combined with molecular dynamics simulations to provide atomic scale insight into the underlying structural changes (Arnlund et al, 2014;Berntsson et al, 2017;Brinkmann and Hub, 2016;Takala et al, 2014).…”
Section: Discussionmentioning
confidence: 99%